Macro Factors and Bond Returns in China. Issue 7 (28th May 2022) - Li, Xinting; Yang, Baochen; Su, Yunpeng; Qi, Yawei; An, Yunbi
ABSTRACT: As a central issue in macro-finance studies, the spanning hypothesis has always been the focus of research. Previous studies have focused on whether this hypothesis holds true in developed markets, while paying little attention to that in emerging markets. Because of their unique monetary systems, governments in most emerging markets play a key role in bond returns. This study identifies macroeconomic factors for forecasting excess returns in emerging government bond markets under spanning hypothesis. We find that in previous research, government intervention factors employed in excess returns forecasting have no additional predictive ability, as they are already incorporated in current yields. Using dynamic factor analysis, we find that macroeconomic information, including pure macroeconomic activities and financial factors, has robust incremental predictive power for in-sample and out-of-sample bond excess returns.